Penyusunan Dan Penerapan Sistem Pencatatan Akuntansi Pada Wash House Laundry - Hendi Hendi; Juliany Susanti (Universitas Internasional Batam, 2021)
The author conducted work practices at the Wash House Laundry from August 2020 to December 2020 with the aim of designing a manual or computer-based accounting recording system using microsoft access. Due to the obstacles that arise in the Wash House Laundry, it is still not recording transactions in detail using an accounting recording system that is in accordance with financial accounting standards, but only records cash receipts and disbursements of laundry manually based on collected notes. So that the profit and loss generated by Wash House Laundry is only based on the calculation of cash receipts and disbursements on a daily basis. The solution that the author can offer is to design and implement a structured accounting recording system that is in accordance with applicable financial accounting standards. As well as accompanying supervisors to improve their understanding and ability to practice the accounting recording system.